Inhabitation Effect of Linoleic Acid, the Ingredient of Nigella sativa (Black Seed) on MDA-MB-231 and MCF-7 Human Breast Cancer Cells - Kourosh Hasanzadeh Ghahramanloo; Latiffah A. Latiff; Parichehr Hanachi; Nordin Hj Lajis (Tehran University of Medical Sciences, 2010)
Objective: The objective of this study was to investigate inhibition and anti-cancer effects of Linoleic acid on the MCF-7 and MDA-MB-231 human breast cancer cells. Materials and methods: Cell lines Human breast cancer MCF-7 (GDC055) and MDA-MB-231 (HTB-26) cell lines were obtained from ATCC. MCF-7 estrogen receptor positive human breast cancer cell line and  the estrogen receptor negative human breast cancer cell line MDA-MB-231, were grown in DMEM. MDA-MB-231 and MCF-7 human breast cancer cell lines were observed. For each experiment, seven doses were considered diluting from the highest to the lowest doses by half, respectively. MTS apoptosis  and cytotoxic activity assay were used in order to find toxic effects, and the results were supported by flow cytometry (Cell cycle analysis). Results: The results showed the cytotoxic effect of Linoleic acid on the breast cancer cell lines that can be posed as an anti-cancer effect of lionleic acid. According to our findings, when the concentration of lionleic acid was increased, compared with the concentrations currently being reported, it shows anti-cancer effects. Conclusion: It was concluded that Linoleic acid has an inhibiting effect on human breast cancer cell lines which can be due to its two double-bandings molecular structure.